Case Report: Transcatheter Aortic Valve Replacement in a Patient With Severe Aortic Stenosis, Left Ventricular Dysfunction, and an Anomalous Left Circumflex Artery - Aldauig, Badreyah; El-Sabbah, Mohammed; Alasnag, Mirvat (Frontiers in Cardiovascular Medicine, 2021)
The role of cardiac computed tomography in the evaluation of patients for transcatheter aortic valve implantation is well established. However, its role in the evaluation of anomalous vessels in the pre-procedure planning, intra-procedural fusion imaging and post-procedure assessment of vessel patency is not yet defined. This case report illustrates the utility of cardiac CT throughout the management of complex structural interventions. Here, we describe an anomalous left coronary artery where the course of the anomalous vessel and its proximity to the aortic valve annulus is defined allowing the selection of the most appropriate balloon expandable valve with a planned deployment. Upon follow up, patency of this anomalous vessel is ascertained using CT as well as the transcatheter valve function and leaflet thickening.